2010
DOI: 10.1111/j.1600-0668.2010.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of PM2.5 and associated elements and their indoor/outdoor pollution status in an urban area

Abstract: An improved understanding of the factors affecting the indoor PM2.5 concentration levels can lead to the development of an efficient management strategy to control health risks from exposure to indoor PM2.5 and related toxic components. A comparison of our comprehensive data sets indicated that most indoor PM2.5 and associated elemental species were strongly enriched by indoor source activities along with infiltration of ambient outdoor air for a naturally ventilated building.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 64 publications
3
31
0
1
Order By: Relevance
“…6(1), [23][24][25][26][27][28][29][30][31][32]2012 (Lim et al, 2011). In relatively clear areas like Deokjeok and Gosan in Korea concentrations of PM 2.5 were somewhat comparable with our data such as 25.3±22.6 and 17.2±10.8 μg m al., 2009).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…6(1), [23][24][25][26][27][28][29][30][31][32]2012 (Lim et al, 2011). In relatively clear areas like Deokjeok and Gosan in Korea concentrations of PM 2.5 were somewhat comparable with our data such as 25.3±22.6 and 17.2±10.8 μg m al., 2009).…”
supporting
confidence: 72%
“…The results yielded five source components, namely PC1 through PC5 which accounted for 30.6, 14.0, 13.3, 10.3, and 7.89% of the total valiance (Table 4) (Karnae and John, 2011). A predominance of such sources as soil dust, traffic, oil/coal combustion, and road dust was seen in outdoor microenvironment in Daejon, one of the major cities in Korea (Lim et al, 2011). The second main source (PC2) appears to be affected by the secondary nitrate with high 'r' value of NO 2 (0.73), NO x (0.80), and CO (0.66).…”
Section: Source Identification Of Constituents Ofmentioning
confidence: 98%
“…The indoor/outdoor relationship studies of PM species showed that major chemical components, including organic and elemental carbon (OC/EC), water soluble ions, and metal elements in indoor PM 2.5 were greatly influenced by outdoor sources (Lim et al, 2011;Cao et al, 2012;Hassanvand et al, 2014). For trace organic matter (OM), however, polycyclic aromatic hydrocarbons (PAHs) were affected by both outdoor sources and heating processes inside apartments (Romagnoli et al, 2014), and phthalic acid esters (PAEs) were dominated by indoor sources .…”
Section: Introductionmentioning
confidence: 99%
“…여 종의 유해 화학물질을 포함하고 있는 것은 물론, 많은 양의 미립자 를 포함하고 있어 실내의 미세먼지 농도를 증가시킨다 [3]. 미립자(fine particle)는 학술 문헌상으로 실내공기 중 이중 모델 (bimodel)에 의하여 0.1~0.2 µm 이하의 입자상 물질로 정의하고, 보 다 큰 조립자(coarse particle)는 20 µm 이상의 입자상 물질로 정의된 다 [4].…”
Section: 서 론unclassified